2000
DOI: 10.1212/wnl.55.9.1271
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of agitation in AD

Abstract: Comparable modest reductions in agitation occurred in patients receiving haloperidol, trazodone, BMT, and placebo. More effective pharmacologic, nonpharmacologic, and combination treatments are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
188
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(194 citation statements)
references
References 33 publications
3
188
0
3
Order By: Relevance
“…All three "weak" studies lost points because of high attrition rates (Cohen-Mansfield and Werner, 1997;Toseland et al, 1997;Teri et al, 2000). Details are presented below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three "weak" studies lost points because of high attrition rates (Cohen-Mansfield and Werner, 1997;Toseland et al, 1997;Teri et al, 2000). Details are presented below.…”
Section: Resultsmentioning
confidence: 99%
“…While there were trends in this direction (Wells et al, 2000;Gormley et al, 2001;Sloane et al, 2004), the outcomes were not striking. In the largest study, Teri et al (2000) compared two medications, an antipsychotic and an antidepressant, with a family behavior management training program. None worked better than a placebo tablet.…”
Section: Treatmentsmentioning
confidence: 99%
“…In another meta-analysis, Lonergan et al (2001) found that haloperidol was beneficial for dementia patients with aggression, but not for general agitation (ie wandering, verbal agitation, etc). Similarly, in recent trials, no significant therapeutic effects were found for haloperidol compared with placebo and trazodone (Teri et al, 2000), compared with placebo and quetiapine (Tariot et al, 2006), and compared with risperidone and placebo (De Deyn et al, 1999). Some, although not all, RCTs with risperidone, olanzapine, and aripiprazole have shown modest efficacy for reducing aggression and overall agitation in AD (Ballard and Waite, 2006;Sink et al, 2005).…”
Section: Agitationmentioning
confidence: 94%
“…46,47 However, another study suggested that its efficacy was similar to placebo. 48 Pharmacological treatment of sexually disinhibited behaviours There are no drugs currently licensed in the UK for sexually disinhibited behaviours; neuroleptics, anti-androgens, oestrogens, LHRH analogues, serotonergics and gabapentin are occasionally used off-licence. 5 There is scarce evidence for neuroleptics.…”
Section: Anticonvulsantsmentioning
confidence: 99%